Responses of tidal duration asymmetry to morphological changes in Lingding Bay of the Pearl River Estuary - Yang, Qingshu; Hu, Shuai; Fu, Linxi; Zhang, Ping; Chu, Nanyang; Liu, Feng; Cai, Huayang (Frontiers in Marine Science, 2022)
Tidal asymmetry is one of the main factors for generating net transport for waterborne materials in tidal estuaries, and thus, this phenomenon has significant influences on controlling morphological development and the ecological environment. Tidal propagation is sensitive to changes in the coastline and geometry of estuarine regions. Moreover, tidal waveforms vary with various factors, such as coastline changes and bathymetry evolution due to local anthropogenic activities. The topography of Lingding Bay (LDB) of the Pearl River Estuary (PRE) has greatly changed since the 1960s because of human interventions, but the response of tidal duration asymmetry (TDA) to morphological changes is still poorly understood. Utilizing the two-dimensional Delft-3D flexible mesh numerical model, the spatial pattern of TDA and its primary contributors in LDB of the PRE were reproduced for 1964, 1989, and 2016, accounting for the changes in both shoreline and bathymetry owing to human interventions. The results reveal that as the tidal wave propagates upstream, the tidal skewness increases from negative values to positive values longitudinally, indicating the transition from a shorter ebb-duration state to a shorter flood-duration state. Additionally, a prominent shift in TDA and its primary contributors takes place approximately in the period of 1989. In 1964-1989, the tidal skewness increased by at least 0.1 throughout the LDB, indicating that the flood duration of the entire bay was shortened significantly. However, in 1989-2016, the tidal skewness decreased by at most 0.15 throughout the LDB, representing a longer flood duration in the entire LDB. The scenario simulations reveal that reclamation-induced shoreline changes control the increase in TDA and its primary contributors by enhancing width convergence of estuary in the period of 1964-1989. Conversely, the increase in water depth plays a vital role in the decrease of TDA in the period of 1989-2016. The results obtained from this study are particularly useful for understanding the controlled factors contributing to net sediment transport and the associated long-term morphological evolution in estuaries heavily impacted by human interventions.